ANALISIS PERILAKU, HUBUNGAN, DAN PERSEBARAN GAME STREAMER PADA MEDIA SOSIAL FACEBOOK - Bianda Reyhan Kesuma; Gita Krismurti Romadhani; Mohammad Refi Nur Ghozi; Shabrina Luthfiani Khanza; Muhammad Khutama Wijaya; Nur Aini Rakhmawati (Universitas Multimedia Nusantara, 2020)
The phenomenon of game streaming is not a brand new subject to video game fans. Game streaming is one of the cutting-edge recreational activities to give a new experience on playing video game, both for game streamers and game stream viewers. In this paper, an analysis is conducted to find out how the behavior, relationships, and distribution of the game streamer on the Facebook Gaming platform in presenting the game streaming. The result of the analysis is that the game streamers are quite active in doing live streaming and interacting with each other game streamers. In addition, the distribution of game streamers tends to be dominated by men aged 20-30 years. Furthermore, the results of this paper are intended to add meaningful insights to the reader.